12.3k views
1 vote
Rearrange the formula to highlight the height

Rearrange the formula to highlight the height-example-1
User Beezer
by
5.3k points

1 Answer

2 votes

Answer:


h = (2A)/(b+c)

Explanation:

Original Equation:


A = (1)/(2) (b+c)h

Divide both sides by height


(A)/(h) = (1)/(2)(b+c)

Raise both sides to the exponent -1 :


((A)/(h))^(-1) = ((1)/(2)(b+c))^(-1)

Rewrite using the definition of a negative exponent:
((a)/(b))^(-x) = ((b)/(a))^(x)


(h)/(A) = (1)/((1)/(2)(b+c))\\

Multiply 1/2 by (b+c)


(h)/(A) = (1)/((b+c)/(2))\\

Keep, change, flip


(h)/(A) = (1)/(1) * (2)/(b+c) = (2)/(b+c)

Multiply both sides by A


h = (2A)/(b+c)

Also I forgot to mention but the exponent (-1) can be ignored after you flip it, since:
((a)/(b))^x = (a^x)/(b^x), but since in our case the exponent is 1, and
a^1 = a, so there's really no need to write out the distribution part, since we just get the same fraction, after flipping it.

User Sumit Bisht
by
4.7k points